Carved in stone, etched in memory death, tombstones and commemoration in Bosnian Islam since c. 1500 - Buturović, Amila 1963- (Farnham, Surrey, England Ashgate Publishing Limited, 2015)
"Gravestones are seen as cultural spaces that inscribe memory, history, and heritage in addition to being texts that display first-hand information about the deceased. This book underscores the importance of material culture, specifically gravestones, funerary inscriptions and images, in tracing and understanding more subtle changes in Bosnia's religious landscape and the complex cultural shifts and exchange between Christianity and Islam in this area. Drawing upon several disciplinary methods, the book has much to offer anyone looking for a better understanding of the intersection of Christianity and Islam, as well as those with an interest in death studies"--Provided by publisher
Appendix: Stone speaker : a visual and reflective travelogue through the deathscape of Bosnia and Herzegovina
Includes bibliographical references and index
Keywords: Muslims -- Social life and customs -- Bosnia and Herzegovina; Death -- Social aspects -- History -- Bosnia and Herzegovina; Death -- Religious aspects -- Islam -- History; Sepulchral monuments -- History -- Bosnia and Herzegovina; Memorials -- History -- Bosnia and Herzegovina; Islamic funeral rites and ceremonies -- History -- Bosnia and Herzegovina; Material Culture -- History -- Bosnia and Herzegovina; Islam -- Relations -- Christianity -- History; Christianity and other religions -- Islam -- History; Bosnia and Herzegovina -- Religious life and customs